Social media activities to enhance the visibility of long-term invasive ventilation: A content and visibility analysis from the PRiVENT study - Franziska C. Trudzinski; Nicola Litke; Olaf Buntemeyer; Simone Janssen; Elena Biehler; Thomas Fleischhauer; Jana C. Dahlhoff; Philipp Höger; Axel Kempa; Benjamin Neetz; Biljana Joves; Claus Neurohr; et al. (PLoS ONE, 2026)
Background Despite the increasing number of patients receiving long-term invasive mechanical ventilation (IMV) and the social importance of this issue, it is largely neglected in the public perception. One aim of the PRIVENT project was to raise public awareness of the issue. Methods A team of physicians, health researchers, an art director and a scientific editor developed an information campaign, including blog posts, podcasts, social media posts and information for medical professionals or patients/their relatives and made them available to the public on a dedicated homepage and various social media platforms. The number of views was used to measure the reach of the campaign. Results In the period from 02/2021–03/2025, a total of 72 blog posts and 880 social media posts and 3 podcast seasons with 21 episodes were made available to the public. The total reach was 2.6 million, with Facebook, Instagram and LinkedIn being the most used platforms with a total of 1872 followers. The most popular blog posts were those that explained the basics of IMV in plain language. Followers of the different social networks differ. Instagram users are younger and more likely to be female than those on Facebook and LinkedIn. Conclusion Our analysis shows that social media can increase the visibility of long-term invasive mechanical ventilation and reach diverse audiences. Although visibility does not equate to awareness, these findings highlight the potential of social media to support broader communication about long-term IMV and weaning within the medical community and society. Trial registration number: The PRiVENT study is registered at ClinicalTrials.gov (NCT05260853) on 02/03/2022.